Paradigma pendidikan agama dalam masyarakat plural - Ju'subaidi Ju'subaidi; Noeng Muhadjir; Sumarno Sumarno (Graduate School, Universitas Negeri Yogyakarta, 2016)
Penelitian ini bertujuan mengungkap paradigma yang mendasari pelaksanaan pendidikan agama di sekolah pluralistik, dan menghasilkan paradigma pendididikan agama yang lebih relevan dengan masyarakat Indonesia yang pluralistik. Desain penelitian ini adalah penelitian deskriptif eksploratif dengan menggunakan pendekatan kualitatif intepretif fenomenologi. Pengumpulan data dengan wawancara mendalam didukung dengan observasi dan dokumentasi. Analisis data menggunakan analisis interaktif yang meliputi reduksi data, display data dan kesimpulan. Di samping itu, juga menggunakan Interpretive Phenomenolgy Analysis. Hasil penelitian adalah Pelaksanaan pendidikan agama konvensional di sekolah yang pluralistik belum mengikuti Peraturan Pemerintah Nomor 55 Tahun 2007 dan PERMENAG Nomor 16 Tahun 2010 tentang Pengelolaan Pendidikan Agama pada Sekolah. Paradigma yang mendasari pendidikan agama adalah eksklusif dan inklusif. Paradigma pendidikan agama yang relevan dengan kondisi bangsa Indonesia yang pluralistik adalah paradigma budaya pluralisme demokratis-emansipatoris.Kata kunci: paradigma, eksklusif, inklusif, konvensional, phenomenology, demokratis-emansipatoris THE PARADIGM OF RELIGION EDUCATION IN A PLURAL COMMUNITYAbstractThis study was to uncover the paradigm that became the basis of the implementation of conventional religion education in the pluralistic schools and to generate a religion education paradigm that would be more relevant to the pluralistic Indonesian society. The approach that the researcher employed in the study was the qualitative interpretative phenomenology. The data were collected through an in-depth interview, and the in-depth interview was supported by an observation and documentation. Then, for the data analysis the researcher implemented the interactive analysis that included data reduction, data display and conclusion. In addition, the researcher also implemented the Interpretive Phenomenology Analysis. The results of the study show that the implementation of conventional religion education in the pluralistic schools has not fulfilled the requirements of the Government Regulation Number 55 Year 2007 and the Minister of Religion Decree Number 16 Year 2010 about the Management of Religion Education in the School. The paradigm that becomes the basis of religion education is the exclusive and inclusive education. The religion education paradigm that is relevant to the conditions of pluralistic Indonesian society is the one which is democratic-emancipative, and pluralistic.Keyword: paradigm, exclusive, inclusive, conventional, phenomenology, democratic-emancipatory